2018
DOI: 10.5089/9781484381632.001
|View full text |Cite
|
Sign up to set email alerts
|

The Price and Welfare Effects of The Value-Added Tax: Evidence from Mexico

Abstract: In this paper we analyze the incidence of the VAT and its effects on the income distribution. To identify these effects, we rely on two tax reforms undertaken in Mexico that increased the VAT rate for a group of cities and left the rest unaffected. We compare the inflation rate of the affected cities with the exempted cities before and after the law changed. We find that the effect on prices is limited and conclude that the burden of the tax is indeed shared between producers and consumers. Regarding welfare, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
1
11
0
1
Order By: Relevance
“…To avoid potential cross-location spillovers, we focus on non-tradable products following the classification in Mariscal and Werner (2018), and in line with recent studies on VAT pass-through (Benzarti and Carloni, 2019;Harju et al, 2018). 30 Our estimation sample contains 291,840 (160,368) product-location-month price observations in traditional (modern) stores.…”
Section: Set-up and Resultsmentioning
confidence: 99%
“…To avoid potential cross-location spillovers, we focus on non-tradable products following the classification in Mariscal and Werner (2018), and in line with recent studies on VAT pass-through (Benzarti and Carloni, 2019;Harju et al, 2018). 30 Our estimation sample contains 291,840 (160,368) product-location-month price observations in traditional (modern) stores.…”
Section: Set-up and Resultsmentioning
confidence: 99%
“…A substantial literature exists estimating the effects of specific tax changes. Carbonnier (2007) considers the impact of decreasing VAT on cars and housing repairs in France; consider a VAT cut for French restaurants, Mariscal and Werner (2018) consider the impact of differences in VAT for Mexican border cities, and Gaarder ( 2018) considers a cut in the VAT on food in Norway. A few studies consider effects across multiple countries: while focus on changes in the VAT on hairdressing in Finland, they also consider all VAT changes across EU member states, and Andrade et al (2015) consider the impact on French export prices of VAT changes in several destination markets.…”
Section: Appendix: Literature Review and Additional Findings A Related Literaturementioning
confidence: 99%
“…Ref. [33] analysed the incidence of VAT in Mexico following two tax reforms that increased the VAT rate for a group of cities and left the rest unaffected. They compared the inflation rate in the affected cities with that in the exempted cities before and after the law changed, found that the effect on prices was limited and concluded that the burden of the tax was shared between producers and consumers.…”
Section: Literature Reviewmentioning
confidence: 99%